Direct stenting versus stenting after predilatation in STEMI patients with high thrombus burden: a subanalysis from the randomized COMPARE CRUSH trial. (3rd October 2022) - Vogel, R F; Delewi, R; Wilschut, J M; Lemmert, M E; Diletti, R; Nuis, R J; Paradies, V; Alexopoulos, D; Zijlstra, F; Montalescot, G; Angiolillo, D J; Krucoff, M W; et al.
Abstract: Background/Introduction: Direct stenting has been proposed to reduce vessel wall damage and distal embolization in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). However, studies comparing direct stenting with stenting after predilatation have shown mixed results so far. Patients presenting with high thrombus burden in the culprit lesion represent a subgroup of STEMI patients that may particularly benefit from direct stenting, as high thrombus burden is associated with suboptimal reperfusion and poor clinical outcomes. Purpose: We sought to determine the efficacy of direct stenting compared with stenting after predilatation in STEMI patients presenting with high thrombus burden. Methods: The randomized COMPARE CRUSH trial assessed the efficacy of pre-hospital administration of crushed versus integral prasugrel tablets in patients presenting with STEMI planned for primary PCI. We assessed Thrombolysis In Myocardial Infarction (TIMI) flow, corrected TIMI frame count (cTFC) and myocardial blush grade at the end of primary PCI, as well as the occurrence of complete (≥70%) ST-segment resolution 1 hour post-PCI in STEMI patients presenting with high thrombus burden in the culprit lesion (defined as a TIMI thrombus grade ≥3). Results: A total of 417 STEMI patients were included in the current analysis of which 336 (81%) presented with high thrombus burden on initial angiography with 144 patients (43%) being treated with direct stenting. Patients undergoing direct stenting exhibited significantly lower cTFC post-PCI compared with stenting after predilatation (16 [12–24] vs. 20 [13–29], p=0.02). Moreover, direct stenting patients more frequently exhibited complete ST-segment resolution 1 hour post-PCI compared with stenting after predilatation (72% vs. 59%, OR 1.82 [95% CI, 1.11–2.99], p=0.02). In contrast, we found no differences in the occurrence of TIMI 3 flow (DS 92% vs. 92%, OR 1.02 [0.47–2.22], p=0.97) or myocardial blush grade 3 (DS 63% vs. 54%, OR 1.45 [95% CI, 0.83–2.52], p=0.19) post-PCI between groups. Conclusion: STEMI patients presenting with high thrombus burden treated with direct stenting showed improved markers of early myocardial reperfusion compared with patients treated with stenting after predilatation, indicating that a direct stenting strategy may benefit the subgroup of STEMI patients that present with high thrombus burden. Randomized trials are warranted to further investigate whether the potential benefits of direct stenting outweigh potential hazards over the long-term. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Daiichi-Sankyo and Shanghai MicroPort Medical